A role for mitogen- and stress-activated kinase 1 in L-DOPA-induced dyskinesia and ΔFosB expression - Feyder, Michael (Biol Psychiatry, 2014)
BACKGROUND: Abnormal regulation of extracellular signal-regulated kinases 1 and 2 (ERK) has been implicated in L-DOPA-induced dyskinesia (LID), a motor complication affecting Parkinson’s disease (PD) patients subjected to standard pharmacotherapy. We examined the involvement in LID of the mitogen- and stress-activated kinase 1 (MSK1), a downstream target of ERK and an important regulator of transcription. METHODS: MSK1 knockout (MSK1 KO) mice and ΔFosB- or ΔcJun-overexpressing transgenic mice were lesioned with 6-hydroxydopamine to produce a model of PD and assessed for LID following chronic L-DOPA administration. Biochemical processes were evaluated by Western blotting or immunoflourescence. Histone H3 phosphorylation was analyzed by chromatin immunoprecipitation (ChIP) followed by promotor-specific quantitative PCR. RESULTS: Genetic inactivation of MSK1 attenuated LID and reduced the phosphorylation of histone H3 at Ser10 in the striatum. ChIP analysis showed that this reduction occurred at the level of the fosB gene promoter. In line with this observation, the accumulation of ΔFosB produced by chronic L-DOPA was reduced in MSK1 KO. Moreover, inducible overexpression of ΔFosB in striatonigral medium spiny neurons exacerbated dyskinetic behavior, whereas overexpression of ΔcJun, which reduces ΔFosB-dependent transcriptional activation, counteracted LID. CONCLUSIONS: These results indicate that abnormal regulation of MSK1 contributes to the development of LID and to the concomitant increase in striatal ΔFosB, which may occur via increased histone H3 phosphorylation at the fosB promoter. They also show that accumulation of ΔFosB in striatonigral neurons is causally related to the development of dyskinesia.